The incidence of psoriasis in Chile: an analysis of the National Waiting List Repository. (1st October 2021) - Lecaros, C.; Dunstan, J.; Villena, F.; Ashcroft, D. M.; Parisi, R.; Griffiths, C. E. M.; Härtel, S.; Maul, J. T.; De la Cruz, C.
Summary: Background: Psoriasis is a serious and chronic noncommunicable disease. However, the fundamental measure of disease occurrence, the incidence, has been scarcely reported globally. There are no previous studies of psoriasis incidence in Latin America. Aim: To estimate the incidence rates of psoriasis in Chile during 2016 and 2017 using an administrative database, the Waiting List Repository. Methods: We examined referrals of psoriasis at onset, made by physicians to dermatologists, evaluated the agreement of diagnosis, and estimated the incidence of the disease considering the eligible population at risk. Results: In most cases, the referrals corresponded to incident cases of psoriasis (73.3%; 95% CI: 66.6–79.2). The national incidence rates of psoriasis were 22.1 (95% CI: 21.1–23.1) and 22.7 (95% CI: 21.8–23.6) per 100 000 person‐years in 2016 and 2017, respectively. The most common type of psoriasis was the late‐onset type. We observed a high variation in the figures throughout the country, with a range from 0.75 (95% CI: 0.3–1.5) per 100 000 person‐years in the Metropolitan region to 164.9 (95% CI: 138.6–195.1) per 100 000 person‐years in the Aysen region. Conclusion: We describe for the first time the incidence of psoriasis in a Latin American country. Our findings could potentially guide collaborations to improve our global understanding of psoriasis in Latin America.